Desenvolvimento micelial de Lentinula edodes em meios de cultivo à base de diferentes substratos orgânicos - Vieira, Lorena; De Aguiar, Bentolila; Sales-Campos, Ceci; Melo De Carvalho, Cristiane Suely [UNESP]; De Almeida Minhoni, Marli Teixeira [UNESP]; Nogueira de Andrade, Meire Cristina [UNESP] (My University, 2011)
The radial mycelial growth of Lentinula edodes (Berk.) Pegler, strain LE-96/13, was studied in culture media prepared with organic residues extract, by using substrates prepared with pineapple (Ananas comosus (L.) Merril) crown, Astrocaryum aculeatum Meyer peel, Theobroma grandiflorum Schum shell, Musa sp. (genomic group AAB, subgroup Pacovan) peel, and Musa sp. (genomic group AAB, subgroup Prata) peel, with three supplementation levels with wheat bran (0, 10 and 20%), and incubated at 25°C. The experimental design was totally randomized, in a 5×3 factorial scheme, adding up 15 treatments with 4 repetitions, and each repetition corresponding to a Petri dish. The diameter of the colony was evaluated daily during nine days of incubation. After that period, it was verified that the highest mycelial growth averages of strain LE-96/13 of L. edodes were found in culture media prepared with T. grandiflorum Schum shell (whose supplementation with wheat bran was favorable for Mushroom development) and A. aculeatum Meyer peel (whose supplementation did not favor the mycelial growth of L. edodes in relation to the medium not supplemented).
Mycelial development of Lentinula edodes in culture media with different organic substrates